2004
DOI: 10.1039/b313199h
|View full text |Cite
|
Sign up to set email alerts
|

The suppression of immunity by ultraviolet radiation: UVA, nitric oxide and DNA damage

Abstract: We have examined the mechanism by which solar-simulated ultraviolet radiation (ssUV) suppresses memory immunity to nickel in allergic humans. In initial studies, we used inbred mice to determine the contribution of different wavebands to sunlight-induced immunosuppression. We found that low dose UVA can enhance memory, medium dose UVA (half the amount in one minimum erythemal dose of ssUV) is immunosuppressive, but higher doses protect from UVB. This is genetically dependent, as it is not observed in all mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…Our studies in hairless mice showed that topical application of 1,25D reduced systemic immune suppression measured 2 weeks after the UV exposure [25], though 1,25D can be immunosuppressive under other conditions [30]. Since increased CPD and reactive nitrogen species both contribute to UV-induced immunosuppression [11,31], it is likely that both the reduced CPD and reduced reactive nitrogen species measured post-UV in the presence of 1,25D contribute to the reduced immunosuppression. An altered cytokine profile is probably a downstream effect [32].…”
Section: Protection From Uv-induced Immune Suppressionmentioning
confidence: 83%
“…Our studies in hairless mice showed that topical application of 1,25D reduced systemic immune suppression measured 2 weeks after the UV exposure [25], though 1,25D can be immunosuppressive under other conditions [30]. Since increased CPD and reactive nitrogen species both contribute to UV-induced immunosuppression [11,31], it is likely that both the reduced CPD and reduced reactive nitrogen species measured post-UV in the presence of 1,25D contribute to the reduced immunosuppression. An altered cytokine profile is probably a downstream effect [32].…”
Section: Protection From Uv-induced Immune Suppressionmentioning
confidence: 83%
“…On the other hand, uncontrolled exposure to UV radiation can cause multiple dermal disorders such as skin cancer, erythema, melanoma, photoaging, etc. All of them may stimulate numerous processes associated to premature aging such as depigmentation, folds and distortions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…According to studies, the UVA effect is very intricate and shows a strong genetic dependence. Medium doses modulate immunity; higher doses can protect the immune system from the suppressive effect of UVB, while lower doses (below 840 mJ/cm 2 ) of UVA can enhance the memory of cell development 29 . Photoaging includes a complex of biologic processes affecting various layers of the skin with the major damage seen in the cognitive tissue of the dermis 30 .…”
mentioning
confidence: 99%